Distinctive sedimentary processes on two contrasting tidal flats of the Yellow River Delta - Xie, Weiming; Sun, Jianwei; Guo, Leicheng; Xu, Fan; Wang, Xianye; Ji, Hongyu; Fan, Yaoshen; Wang, Zheng Bing; He, Qing (Frontiers in Marine Science, 2023)
Coastal tidal flats provide valuable ecosystems, but are highly sensitive to tidal dynamics, sea-level rise, and human activities. Tidal inundation depth and frequency are known to affect tidal flat morphodynamics. However, the causes, processes and extent remain uncertain, particularly given the associated changes in sediment availability. In this study, we monitored the hydrodynamics, sediment transport, and morphological changes on two tidal flats in the northern and southern parts of the Yellow River Delta, with contrasting tidal regimes. The data showed that longer inundation periods under diurnal tides gained additional sediment and deposition than under semi-diurnal tides, because of the associated increase in water depth and sediment availability. The wave impact increased at the site with a semi-diurnal tidal regime owing to the lower water depth, where a larger bed shear stress led to tidal flat erosion. These results indicated that the combination of tidal regime and the occurrence of powerful waves played a joint role in controlling bed erosion, sediment availability, and short-term tidal flat evolution. This has implications for coping with delta erosion by enhancing local sediment availability in diurnal tidal regions and restoring vegetation to attenuate waves in semi-diurnal regions of the Yellow River Delta.